Trends in burden of cirrhosis and hepatocellular carcinoma by underlying liver disease in US veterans, 2001-2013 - Beste, Lauren A; Leipertz, Steven L; Green, Pamela K; Dominitz, Jason A; Ross, David; Ioannou, George N (Gastroenterology (New York, N.Y. 1943), 2015)
Cirrhosis and hepatocellular carcinoma (HCC) are predicted to increase in the United States but the accuracy of prior forecasts and the contributions from various liver disease etiologies remain unclear. We aimed to determine the burden of cirrhosis and HCC according to underlying cause from 2001 to 2013. We developed a national retrospective cohort of Veterans Affairs (VA) patients with the diagnosis of cirrhosis (n = 129,998) or HCC (n = 21,326) from 2001 to 2013. We used laboratory results, International Classification of Diseases, ninth edition (ICD-9) codes, and body mass index to identify underlying etiologies. In 2013, VA provided care to 5,720,614 individuals, of whom 60,553 (1.06%) had cirrhosis and 7,670 (0.13%) had HCC. Hepatitis C virus (HCV) was present in an increasing proportion of cirrhosis and HCC between 2001 and 2013, reaching 48% of cirrhosis cases and deaths and 67% of HCC cases and deaths by 2013. Cirrhosis prevalence nearly doubled from 2001 to 2013 (664 to 1058 per 100,000 enrollees), driven by HCV and nonalcoholic fatty liver disease (NAFLD). Cirrhosis incidence ranged from 159 to 193 per 100,000 patient-years. Deaths in patients with cirrhosis increased from 83 to 126 per 100,000 patient-years, largely driven by HCV. HCC incidence was 2.5-fold increased from 17 to 45 per 100,000 patient-years. HCC mortality tripled from 13 to 37 per 100,000 patient-years, driven overwhelmingly by HCV, with much smaller contributions from NAFLD and alcoholic liver disease. Cirrhosis prevalence and mortality and HCC incidence and mortality increased from 2001 to 2013, driven by HCV, with a smaller contribution from NAFLD. If current trends continue, cirrhosis prevalence will peak in 2021. Health care systems will need to accommodate rising numbers of patients with cirrhosis and HCC.